Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/csc2.20891
|View full text |Cite
|
Sign up to set email alerts
|

Optimally combined application of organic and chemical fertilizers increases grain yield and improves rhizosphere microecological properties in rice ratooning

Abstract: Field tests were conducted at experimental station of Chongluo, Nanping city, Fujian province, China in 2018–2019 to explore the action and physiological mechanism of organic nitrogen in rice ratooning under the configurations with different proportions of organic and inorganic nitrogen. The results showed that sole chemical fertilizer (CF) led to a significant decrease in soil nutrient availability, especially at late growth stage, and reduced grain yield of the main and ratooning crops compared with the opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Mineralization of organic compounds from these fertilizers, spread out over time, causes the gradual release of nitrogen in available forms, which enables a regular supply of this macronutrient to plants. In the case of chemical fertilizers, the entire pool of nitrogen is usually available for plants immediately after their application, but decreases significantly in the later stage of their growth 29 . This is the result of nitrogen being taken up by plants and dissipated in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Mineralization of organic compounds from these fertilizers, spread out over time, causes the gradual release of nitrogen in available forms, which enables a regular supply of this macronutrient to plants. In the case of chemical fertilizers, the entire pool of nitrogen is usually available for plants immediately after their application, but decreases significantly in the later stage of their growth 29 . This is the result of nitrogen being taken up by plants and dissipated in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we replaced 20% of inorganic N fertilizer with organic fertilizer to achieve reduced inorganic N fertilizer management in rice production. Previous studies had reported that the combined application of organic and chemical N fertilizers improved rice production and promoted N accumulation and use ( Zhang et al., 2018 ; Lin et al., 2023 ). The fertilizer of rapeseed cake (RC) is one of the important organic fertilizers that can increase grain yield and NUE by improving soil organic matter and the abundance of microorganisms in the soil ( Zhou TY.…”
Section: Introductionmentioning
confidence: 99%